The roles of HMGB1 related angiogenesis and lymphangiogenesis in oral cancer - Hiroki Kuniyasu; Tomonori Sasahira; Ujjal K. Bhawal; Yoshitomo Chihara; Miyako Kurihara; Kazuhiko Yamamoto; Tadaaki Kirita (Frontiers Media S.A., 2011)
Angiogenesis and lymphangiogenesis are the vital factors in tumor progression and metastasis. In this review, we show that high-mobility group box 1 (HMGB1) is responsible for both angiogenesis and lymphangiogenesis in oral squamous cell carcinoma (OSCC). HMGB1 possesses the dual role as a cytokine and as a chromatin protein. HMGB1 as a cytokine is the ligand of receptor for advanced glycation end products (RAGE). RAGE activation upregulates secretion of vascular endothelial growth factor (VEGF). Then co-expression of HMGB1 and RAGE accelerates angiogenesis. In contrast, nuclear HMGB1 transcriptionally induces the expression of melanoma inhibitory activity (MIA) gene with NFkB. MIA upregulates expression of VEGF-C and VEGF-D via p38 phosphorylation by integrin activation. Then HMGB1 and MIA is associated with lymphangiogenesis. According to the differential roles of HMGB1 on angiogenesis and lymphangiogenesis, local invasion, disease recurrence, and poor prognosis are associated with HMGB1-RAGE system, whereas lymph node metastasis is associated with HMGB1-MIA system in OSCC.